Fsc Part 1 Mathematics (Complete Solution)

Q5
Solve That

If  
 
ι
1
 
 ,B = 
 
1
ι
 
  and C= 
 
-1
ι
 

(i) (AB)C=A(BC)

SOLUTION:

L.H.S=(AB)C

 = ( 
 
ι
1
 
  
 
1
ι
 
 )  
 
-1
ι
 
 = 
 
2+4ι2 ι+2ι2
ι-2ι2 1-ι2
 
  
 
-1
ι
 
   
 = 
 
1-4 ι-2
ι+2 1+1
 
  
 
-1
ι
 
   
 = 
 
-3 ι-2
ι+2 2
 
  
 
-1
ι
 
   
 = 
 
-6ι-ι2+2ι 3+ι2-2ι
-2ι2+4ι-2ι ι-2+2ι
 
  
 = 
 
-4ι+1 -2ι+2
2ι+2 3ι-2
 
  

R.H.S=A(BC)

 =  
 
ι
1
 
 ( 
 
1
ι
 
   
 
-1
ι
 
)
 = 
 
ι
1
 
  
 
-2ι2 ι+ι
22 -2ι+ι2
 
   
 = 
 
ι
1
 
  
 
2-ι 2ι 
-4+1 -2ι-1
 
   
 = 
 
ι
1
 
  
 
2-ι
-3 -2ι_-1
 
   
 = 
 
2ι-ι2-6ι 2-4ι2-2ι
2-ι-6ι 2ι+2ι2
 
  
 = 
 
-4ι+1 -2ι+2
2ι+2 3ι-2
 
  

L.H.S=R.H.S

Hence (AB)C=A(BC)

(ii) (A+B)C=AC+BC

SOLUTION:

L.H.S=(A+B)C

 = ( 
 
ι
1
 
 + 
 
1
ι
 
 )  
 
-1
ι
 
 = 
 
ι-ι 2ι+1
1+2ι -ι+ι
 
  
 
-1
ι
 
   
 = 
 
0 2ι+1
1+2ι 0
 
  
 
-1
ι
 
   
 = 
 
0_2ι2 2
2+2ι -2ι-1
 
 = 
 
-2(-1)-ι 2(-1)+ι
4(-1)+2ι -2ι-1
 
  
 = 
 
2-ι -2+ι
-4+2ι -2ι-1
 
  

R.H.S=AC+BC

 AC=  
 
ι
1
 
  
 
-1
ι
 
 
 = 
 
0 -ι-2
2ι-1 0
 
   
 BC= 
 
1
ι
 
  
 
-1
ι
 
   
 = 
 
2-ι
-5 -2ι-1
 
   
 AC+BC=  
 
0 -ι-2
2ι-1 0
 
 + 
 
2-ι
-5 -2ι-1
 
 
 = 
 
0+2-ι -ι-2+2ι
2ι+1-5 0-2ι-1
 
  
 = 
 
2-ι -2+ι
-4+2ι -2ι-1
 
  

Hence L.H.S=R.H.S

So proved

Other Topics

;